Odpowiedź :
Odpowiedź:
a)
6x = 3
x= 3/6 = 1/2
b)
-3x = 7
3x = - 7
x = -7/3= - 2 1/3
c)
2x = 1/5
x = 1/5 : 2 = 1/5 * 1/2 = 1/10
d)
1,2x = 4,8
x = 4,8 : 1/2 = 4
e)
1/3x = 3
x = 3 * 3 = 9
f)
- 3/5x = - 5
3/5x = 5
x = 5 : 3/5 = 5 * 5/3 = 25/3 = 8 1/3
g)
3/4x = - 4/9
x = - 4/9 : 3/4 = - 4/9 * 4/3 = - 16/27
h)
0,1x = - 7
x = - 7: 0,1 = - 7 : 1/10 = - 7 * 10 = - 70
Odpowiedź:
6x = 3
x = 3 : 6
x = 1/2
spr 6 * 1/2 = 3
-3x = 7
x = - 7 : 3
x = -7/3
x = -7/3
spr -3 * (-7/3) = 7
2x = 1/5
x = 1/5 : 2 = 1/5 * 1/2
x = 1/10
spr 2 * 1/10 = 1/5
1,2x = 4,8
x = 4,8 : 1/2
x = 4
spr 1,2 * 4 = 4,8
1/3x = 3
x = 3 * 3
x = 9
spr 1/3 * 9 = 9/3 = 3
- 3/5x = - 5
x = -5 : (-3/5) = 5 * 5/3
x = 25/3
spr -3/5 * 25/3 = -5
3/4x = -4/9
x = - 4/9 : 3/4 = - 4/9 * 4/3
x = -16/27
spr 3/4 * (-16/27) = -4/9
0,1x = -7
x = - 7: 0,1 = - 7 : 1/10 = - 7 * 10
x = -70
spr 0,1 * (-70) = -7